Color it up! color harmony and children's attention: the use of complementary and split-complementary color schemes on teaching materials for kindergarten students - Otivo, Bianca Natalie L.
Colors have always been a part of our life. We can see it anywhere, everywhere, on something and on someone. It has always been a part of our daily lives, from the moment we wake up until the moment that we close our eyes to sleep, even in our dreams. As artists we see as a very powerful tool for communicating or sharing our views through our works of art. It is amazing that the use of certain colors adds emotions to our works; sometimes, it gives a signal for action, and most of all, it affects the moods of our viewers. Perceptions of colors, although sometimes are subjective, depending on individual experiences or cultural beliefs etc., have universal meanings, for example; the red area of the spectrum also known as the warm colors give a feeling of warmth and comfort to a feeling of anger an hostility while the blue area, or the cool colors give a feeling of calmness, but may also give a feeling of sadness and unimportance. In this study we will be testing how colors affect the attention of children in class. Based on the gathered data and interviews we will be able to make a product that will aid the teachers on choosing the right colors for their teaching materials.